2003
DOI: 10.1521/suli.33.4.400.25235
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Counselling for Adolescent Suicide Prevention: Changes in Suicidality and Mental State from Beginning to End of a Counselling Session

Abstract: Telephone counselling is an accessible and confidential means by which distressed young people can seek help. Telephone counselling services were funded under Australia's National Youth Suicide Prevention Strategy between 1997 and 2000. In this study, the effectiveness of telephone counselling for young people seeking help in the context of suicidal ideation or intent was evaluated in an investigation of calls made by suicidal young people to a telephone counselling service. Independent raters measured callers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 34 publications
4
94
0
Order By: Relevance
“…In attending to a person who has described an intent to take his or her own life or who has already attempted suicide, these emergency personnel may save a caller's life. Recent evaluations of suicide hotlines have generally used objective third-party evaluators who have listened to live or recorded calls and have found that callers experience reduced distress and suicidal thoughts or intent over the course of a call (Gould, Cross, et al, 2013;Gould, Kalafat, et al, 2007;Gould, Munfakh, et al, 2012;King et al, 2003;Mishara and Daigle, 1997;Ramchand, Jaycox, et al, 2016).…”
mentioning
confidence: 99%
“…In attending to a person who has described an intent to take his or her own life or who has already attempted suicide, these emergency personnel may save a caller's life. Recent evaluations of suicide hotlines have generally used objective third-party evaluators who have listened to live or recorded calls and have found that callers experience reduced distress and suicidal thoughts or intent over the course of a call (Gould, Cross, et al, 2013;Gould, Kalafat, et al, 2007;Gould, Munfakh, et al, 2012;King et al, 2003;Mishara and Daigle, 1997;Ramchand, Jaycox, et al, 2016).…”
mentioning
confidence: 99%
“…Only the caller has the authority and responsibility to make decisions about his own life, including the judgement that his best interests are to end it. Unlike many suicide crisis helplines (de Anda and Smith 1993;Mishara 1997;King et al 2003;Barber et al 2004;Kalafat et al 2007;Ingram et al 2008), Samaritans will not advise or actively intervene to deflect a caller who declares intent to die by suicide. Volunteers aim to offer the caller unconditional, nonjudgemental acceptance and support.…”
mentioning
confidence: 99%
“…Previous studies revealed that help offered by telephone or well-known hotline number using reduce suicides significantly. [9][10][11]14,22,32,33 Counseling services can be provided by both trained or untrained counselors in the community level and people in despair are encouraged to contact through a widely published number. 5,14 Befriending approach is used in most of the hotline centres and unguided brief mobile intervention, telephone after care interventions delay and reduce suicide significantly.…”
Section: Hotline Interventionsmentioning
confidence: 99%